Алгебра
Алгебра, 14.10.2019 07:37, pepikhova2

Вопрос/Задача:

X^+x(6-2х)=(х-1)-1 решить уравнение !

Ответы на вопрос

Ответ
Ответ разместил: Гость

ответ:

29

объяснение:

5•n - 3•m

n=4 ; m=(-3)

5•4 - 3•(-3)=

=20-(-9)=

=29

Ответ
Ответ разместил: Гость

2,4 секунды на высоте не менее 9 метров               

Ответ
Ответ разместил: Гость

f(x) = -3x^2 + 10.

а) f(-1) = -3 + 10 = 7.

б) f(0) = 10.

в) f(1/3) = -3*(1/9) + 10 =

Ответ
Ответ разместил: СашаСтоляров1

x²+x(6-2х)=(х-1)-1

x²+6x-2x²=x-1-1

-x²+5x+2=0

x²-5x-2=0

d=25+8=33

Похожие вопросы

Вопросов на сайте: